Problems in 2013 Curriculum Implementation for Classroom Teachers in Madrasah Ibtidaiyah - Muhamad Arif; Sulistianah Sulistianah (UIN Siber Syekh Nurjati Cirebon, 2019)
Abstract2013 curriculum still becomes a problem which needs a solution as soon as possible so that the objectives of the 2013 curriculum can be achieved optimally. Starting from the facts above, encouraging researchers to conduct quite complex and in-depth research about contemporary problems experienced by classroom teachers in the application of the 2013 curriculum in the field and solutions for classroom teachers in facing the implementation problems of 2013 curriculum. In this study, researchers used qualitative methods using several data collection techniques, namely: observation, interviews, and documentation. Data sources in this study focused on classroom teachers. The data analysis technique uses Miles and Huberman. The findings from the research results are quite significant on the contemporary problem of the application of the 2013 curriculum, including 1) government problems, 2) institutional problems, 3) classroom teacher problems, 4) student personal problems, and 5) problems of understanding guardians. While, the solutions for classroom teachers in facing the implementation problems of 2013 curriculum, namely 1) the need for efforts from the government in improving teacher competence, 2) the establishment of cooperation with more competent institutions such as universities, and 3) the establishment of maximum communication between schools, students, and guardians of students with parenting frames. With these efforts, it is expected that the implementation problems of 2013 curriculum in the Islamic elementary school can be overcome.Keyword: classroom teacher, implementation problems, 2013 curriculum. AbstrakKurikulum 2013 masih menyimpan pekerjaan rumah dan perlu mendapatkan solusi secepat mungkin. Hal ini dilakukan agar tujuan dari penerapan kurikulum 2013 dapat tercapai secara maksimal. Berawal dari fakta di atas, memantik peneliti untuk melakukan penelitian yang cukup kompleks dan mendalam mengenai problem-problem kontemporer yang dialami guru kelas dalam penerapan kurikulum 2013 di sekolah, dan solusi guru kelas dalam menghadapi problem implementasi kurikulum 2013. Pada penelitian ini, peneliti menggunakan metode kualitatif dengan menggunakan beberapa teknik pengumpulan data, yaitu: observasi, wawancara, dan dokumentasi. Sumber data pada penelitian ini terfokus pada guru kelas. Teknik analisis data menggunakan Miles dan Huberman. Temuan dari hasil penelitian ini cukup signifikan, yaitu pada problem kontemporer penerapan kurikulum 2013, meliputi 1) problem pemerintah, 2) problem institusi, 3) problem guru kelas, 4) problem pribadi siswa, serta 5) problem pemahaman wali murid. Sementara itu, solusi guru kelas dalam menghadapi problem implementasi kurikulum 2013 yaitu: 1) diperlukannya upaya pemerintah dalam meningkatkan kompetensi guru, 2) terjalinnya kerjasama dengan instansi yang lebih kompeten seperti perguran tinggi, dan 3) terjalinnya komunikasi yang maksimal antara sekolah, siswa, dan wali murid dengan bingkai parenting. Dengan upaya-upaya tersebut, diharapkan problem penerapan kurikulum 2013 di madrasah ibtidaiyah dapat teratasi.Kata kunci: guru kelas, masalah implementasi, kurikulum 2013.